Estágio com pesquisa: narrativas de formadores do curso de licenciatura em Matemática da Universidade Estadual de Goiás - Rocha, Vanessa Amélia da Silva (2020)
This study presents, through a bibliographic review and research from the narratives of trainers in the Mathematics Degree course at the State University of Goiás (UEG), the title "Research Internship: Narratives of Mathematics Degree Course Trainers from Universidade Estadual de Goiás ", because it understands that this is a relevant subject for the training of mathematics teachers. We were motivated by the problem: How did the research internship arrive in the undergraduate course at Universidade Estadual Goiás (UEG), through the voice of teacher educators who work with the Supervised Internship? And for that, the text was structured in the form of a narrative, with the support of the embroidery metaphor, whose intention is to represent the stages of preparation of this study, as if it were step by step The "embroidery" of the research was comprised of four moments, of which: i) Survey and bibliographic analysis; ii) Questionnaire application; iii) Rea semi-structured interviews; and, iv) Analysis of the collected data. In the first moment, the materials for bibliographic review and analysis were raised, culminating in the participation of authors such as Connelly and Clandinin (1995), Clandinin and Conelly (2015), Ghedin, Oliveira and Almeida (2015) and Pimenta; Lima (2012), among others no less important. The second step, we contemplate the stages III and IV of the study, when we verify that the institution has 10 (ten) Campus who offer the course, which totaled 25 (twenty-five) trainers working with the internship, who were invited to participate of the research by answering a questionnaire with open questions, which contained questions about his professional and training profile, as well as about his work with an internship in the mathematics degree. We had the feedback of 10 (ten) teachers and, from these, we selected 2 (two) subjects to carry out semi-structured interviews. Finally, we conducted a narrative analysis of these interviews, which enabled the construction of this research. However, the embroidery of the research allowed to infer, the evidence that, the interviewed trainers, in a certain way, have complied with the curricular guidelines for the training of teachers and worked within the scope of the research internship. Returning to my problem question, we can say that the research internship has reached the Bachelor's Degree in Mathematics at UEG in a simple and reasonable way. However, it is necessary that teachers know how to teach and not only have knowledge. It is also necessary for teacher training to be continuous, given that education undergoes several transformations over time.